2016
DOI: 10.1111/andr.12183
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of attention‐deficit/hyperactivity disorder associated with exposure to organophosphate pesticide in Taiwanese children

Abstract: SUMMARYAttention-deficit/hyperactivity disorder (ADHD) is male predominated, and the etiology of this disorder remains unclear. Past studies have assessed the association of low-level organophosphate pesticide exposure with childhood ADHD cross-sectionally and prospectively. However, the results have been inconsistent. A first case-control study was performed to investigate the relationship between organophosphate pesticide exposure and ADHD with adjusted covariates. We recruited 97 doctor-diagnosed ADHD cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 75 publications
2
35
1
1
Order By: Relevance
“…In contrast to our findings, several previous studies have reported adverse associations between OPs and various measures of executive functioning, including attention, ADHD, and working memory (Bouchard et al, 2010, 2011; Eskenazi et al, 2014; Marks et al, 2010; Rauh et al, 2011, 2006; Yu et al, 2016), although studies examining prenatal exposure originate from only two other cohorts (Bouchard et al, 2011; Marks et al, 2010; Rauh et al, 2011). In the CHAMACOS cohort, Marks et al (Marks et al, 2010) reported associations between ΣDMPs and ΣDEPs and parent-report measures of attention problems at 3.5 but not 5 years, and also associations with a performance-based measure of attention, the Kiddie Connors Performance Test (K-CPT).…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our findings, several previous studies have reported adverse associations between OPs and various measures of executive functioning, including attention, ADHD, and working memory (Bouchard et al, 2010, 2011; Eskenazi et al, 2014; Marks et al, 2010; Rauh et al, 2011, 2006; Yu et al, 2016), although studies examining prenatal exposure originate from only two other cohorts (Bouchard et al, 2011; Marks et al, 2010; Rauh et al, 2011). In the CHAMACOS cohort, Marks et al (Marks et al, 2010) reported associations between ΣDMPs and ΣDEPs and parent-report measures of attention problems at 3.5 but not 5 years, and also associations with a performance-based measure of attention, the Kiddie Connors Performance Test (K-CPT).…”
Section: Discussioncontrasting
confidence: 99%
“…The level of dimethyl phosphate was significantly higher in the children with ADHD compared to controls. 48 Of note, this study measured concurrent pesticide levels, and while the design is case-control, there is no assurance that the concurrent pesticide levels are similar to pesticide levels during critical periods of development. A retrospective cohort study examined associations between ADHD and home residence near several environmental exposures.…”
Section: Role Of Genetics and The Environment And Genetics In Neurocomentioning
confidence: 98%
“…For other SNPs: rs7395429, rs3758653, rs11246228, rs752306 [49][50][51] ; rs4646984 52 ; rs916457 53 ; rs936465 54 , nometa-analyses can be performed, because very few studies were available (minimum three studies), considering that Yu and colleagues 49,50 and Chang and colleagues 51 studied the same population.…”
Section: Newcastle-ottawa Scalementioning
confidence: 99%